Miicrobiiollogiicall Impactt off Diippiing Miinced Meatt usiing diifffferentt sodiium hypochlloriitte concenttrattiion and conttactt ttiimes: Zuhaiir ..A..Mohammad Huda N..Jasiim - Mohammad, Zuhaiir A. (The Iraqi Journal of Veterinary Medicine, 2011)
This study was conducted to evaluate the possibility of using sodiumHypochloride by the Iraqies housewives at different concentrations (2%, 3%)and different dipping times (30, 60 and 90 minutes ) in order to reduce theinitial microbial counts , without any adverse effect on the organolepticcharacteristics of the treated minced meat. Bacterial counts in all samples ofmeat were enumerated by standard method of miles and mirza technique beforeand after treatment .The result showed that the treatment of meat with chlorine at concentration 2% for 30 and 60 minute reduce the bacterial content on bacterial load ( colonyforming unit – cfu / ml) to a level which was significant from the Public healthpoint of view ( hygienically ) although , this reduction was not staticallysignificant, using 2 % for 90 minutes , however , reduced the ( colony formingunit cfu/ ml) about 2 Log , which was highly significant ( P<0.01) statically andhygienically Sodium Hypochlorite at 3 % for 30, 60 , 90 minutes reduced the( Colony forming unit – cfu / ml ) significantly about 2 log (P<0.01, P<0.05,P<0.05 respectively).Results of the effects of different concentrations of sodium hypochlorute atdifferent dipping times (30,60 and 90 minutes ) on the organoleptic charactersof the minced meat showed that , sodium hypochlorite at 2 % for 30 , 60 and 90minutes , and at 3 % minutes reduced the cfu / ml significantly without affectingthe organoleptic charcteristics of treated minced meat , while using 3 % for 60and 90 minutes although reduced the bacterial content on the bacterial loud( colony forming unit-cfu / ml) but adversely affects the organolepticcharacteristics even with different types of spices and herpes using in thetraditional Iraqi cooking .